Returns to Hedge Fund Activism: An International Study - Becht, Marco; Franks, Julian; Grant, Jeremy; Wagner, Hannes F. (Review of Financial Studies, 2017)
This paper provides evidence on the incidence, characteristics, and performance of activist engagements across countries. We find that the incidence of activism is greatest with high institutional ownership, particularly for U.S. institutions. We use a sample of 1,740 activist engagements across 23 countries and find that almost one-quarter of engagements are by multi-activists engaging the same target. These engagements perform strikingly better than single activist engagements. Engagement outcomes, such as board changes and takeovers, vary across countries and significantly contribute to the returns to activism. Japan is an exception, with high initial expectations and low outcomes.